COMPARISON OF FRENULOTOMY VERSUS FRENULECTOMY IN CASES OF ANKYLOGLOSSIA - Khan, Muhammad Ahmed; Akram, Sumera; Usman, Hassan Bin; Ali, Ghazanfar (Journal of Postgraduate Medical Institute, 2018)
Objective: To compare frenulotomy versus frenulectomy in cases of ankylo- glossia in terms of post operative improvement in speech and feeding difficul- ties in children. Methodology: This study was carried out in Combined Military Hospital (CMH), Bahawalpur. Total 64 cases of tongue tie were selected from outpatient depart- ment. The cases were randomly divided into two groups. In group A, children underwent frenulectomy via Z-plasty and in group B they had frenulotomy i.e. release of tongue tie with bipolar diathermy. Postoperative improvement in speech and feeding problems was assessed in both groups. Results: Mean age of children in the study was 2.79 ±1.01 years. There were 45 (70.3%) males and 19 (29.7%) females. Group A, had significantly better im- provement in speech as compared to group B (p =0.000). regarding breast feeding, both procedures showed almost similar improvement (p =0.224). Conclusion: Frenulectomy was superior to frenulotomy as far as post operative speech is concerned; however, both procedures were almost equally effective in improving feeding problems (breast feeding) in babies with tongue ties.